Comparative cost-effectiveness of first-line pembrolizumab plus chemotherapy vs. chemotherapy alone in persistent, recurrent, or metastatic cervical cancer - Lin, Ying-tao; Wang, Chang; He, Xiao-yan; Yao, Qi-min; Chen, Jian (Frontiers in Immunology, 2024)
Background Treating persistent, recurrent, or metastatic cervical cancer remains challenging. Although pembrolizumab, combined with chemotherapy and bevacizumab, offers a promising first-line option, its cost-effectiveness within the Chinese healthcare system has not been established. Methods A partitioned survival model was constructed using patient data from the KEYNOTE-826 trial. Efficacy, safety, and economic data from both trial and real-world practices were utilized to determine the costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratio (ICER) of the treatment strategies. Comprehensive insights were gained through the sensitivity and subgroup analyses. Results Over five years, the combination of pembrolizumab, chemotherapy, and bevacizumab offered an additional 1.18 QALYs compared to that provided by standard treatments. This regimen increased the costs by US$ 134,502.57, resulting in an ICER of US$ 114,275.67 per QALY, relative to traditional treatment costs. The ICER for the pembrolizumab regimen was further calibrated to be US$ 52,765.69 per QALY. Both ICER values surpassed China’s established willingness-to-pay threshold. Importantly, subgroup analysis revealed enhanced cost-effectiveness in patients presenting with a programmed death-ligand 1 combined positive score (PD-L1 CPS) ≥10. Conclusion Introducing pembrolizumab alongside chemotherapy and bevacizumab may not be a cost-effective primary strategy for advanced cervical cancer against current standards. However, for patients with a PD-L1 CPS ≥10, the therapeutic and economic outcomes could be improved by adjusting the pembrolizumab price.